2021
DOI: 10.3389/fcell.2021.699804
|View full text |Cite
|
Sign up to set email alerts
|

A New Ferroptosis-Related lncRNA Signature Predicts the Prognosis of Bladder Cancer Patients

Abstract: Background: Ferroptosis is closely related to the occurrence and development of cancer. An increasing number of studies have induced ferroptosis as a treatment strategy for cancer. However, the predictive value of ferroptosis-related lncRNAs in bladder cancer (BC) still need to be further elucidated. The purpose of this study was to construct a predictive signature based on ferroptosis-related long noncoding RNAs (lncRNAs) to predict the prognosis of BC patients.Methods: We downloaded RNA-seq data and the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…As bioinformatics technology has advanced in recent years, a variety of lncRNA-related signatures have been established to predict the outcome of patients with fatal malignancies such as pancreatic cancer, breast cancer, colorectal cancer, and bladder cancer [ 19 22 ]. Nevertheless, FRL signatures for forecasting the survival and molecular characteristics of HCC are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bioinformatics technology has advanced in recent years, a variety of lncRNA-related signatures have been established to predict the outcome of patients with fatal malignancies such as pancreatic cancer, breast cancer, colorectal cancer, and bladder cancer [ 19 22 ]. Nevertheless, FRL signatures for forecasting the survival and molecular characteristics of HCC are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…to predict the outcome of patients with fatal malignancies such as pancreatic cancer, breast cancer, colorectal cancer, and bladder cancer [19][20][21][22]. Nevertheless, FRL signatures for forecasting the survival and molecular characteristics of HCC are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, an iron-dependent form of nonapoptotic cell death has been proved to be closely related to the development of cancer (27). The ferroptosis-related lncRNA signatures can predict the prognosis of bladder cancer patients, which still needs further experimental verification in the future (28).…”
Section: Discussionmentioning
confidence: 99%
“…There may also be crosstalk between necroptosis and other forms of PCD, such as ferroptosis or pyroptosis [21]. Researchers constructed a 9-ferroptosis-related lncRNAs model to predict the prognosis of patients with BLCA and found that they were more sensitive to anti-PD-1/L1 immunotherapy and chemotherapy drugs, such as sunitinib, paclitaxel, docetaxel, and docetaxel [22]. Recently, an 8-nrlncRNAs prognostic signature associated with pyroptosis was developed to explore the molecular markers of BLCA [23].…”
Section: Discussionmentioning
confidence: 99%